THE PRODUCTION OF MEZCAL IN THE MUNICIPALITY OF DURANGO, MEXICO - Sixto Barraza-Soto; Pedro Antonio Domínguez-Calleros; Eusebio Montiel-Antuna; J. Jesús Návar-Chaidez; Manuel Antonio Díaz-Vásquez (Ra Ximhai, 2014)
In Durango Municipality there are six enterprises which elaborate mezcal, four of them are certified. Row matter is extracted from wild plantations, 72% comes from the fields of the Ejido Nicolás Romero. The possible production of mezcal is 528,092 liters per year; this quantity exceeds 5 times the maximum production projected, according to the installed infrastructure capacity. Certified enterprises have higher production costs but also have better benefits than “vinatas”. The price of a 750 ml mezcal bottle is $138.00 pesos plus tax, while the price of a bottle of the same capacity produced in rustic enterprises fluctuates between $30.00 y $70.00 pesos. Certified enterprises produce the mezcal following the production and packaging criteria of the NOM-070-SCFI-1994. Rustic enterprises do not follow this Rule, storing and selling the product in any kind of bottle either of glass or plastic. The conclusion is that mezcal production is profitable if the producers are associated and certify the product, especially in the production of maguey and in the packaging process. This on one hand would help preserve biodiversity in the sites where the plant is extracted now, and, on the other hand, it would decrease the intervention of intermediaries contributing to obtaining higher incomes for mezcal producers.